CEO POWER, GENDER DIVERSITY AND ESG PERFORMANCE: EVIDENCE FROM FINANCIAL COMPANIES IN ASEAN-5 - Dillak, Vaya; Hapsari, Tarisha (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
ESG principles are considered significant because they do not only focus on increasing profits but also pay attention to environmental, social, and good governance aspects. This research aims at analyzing the influence of CEO power and gender diversity on banking companies that go public in ASEAN-5 countries. This research used a non-probability sampling with a purposive sampling technique to select the sample. This technique obtained 24 banking companies going public in ASEAN-5 countries during 2018-2022. The analysis technique used in this research was panel data regression. The result showed that CEO Power and gender diversity positively affected ESG performance, then the control variable ROA had a negative effect as well Size had a positive effect. On the other hand, DER did not affect ESG Performance. The practical implications of the research results for companies stated that companies could implement CEO Power and gender diversity in the corporate environment to support sustainable development goals.